A Conceptual Model of Change Management for E-Government Project in Indonesia - Sulistiyani, Endang; Susanto, Tony Dwi (IPTEK Journal of Proceedings Series, 2019)
Implementation of e-government projects in developing countries is mostly failed. Current studies found that most of these failures were caused by failure in managing changes. Meanwhile, government as an object of e-government projects in a country, especially Indonesia will provide its own uniqueness, While the current model of change management was still general. Therefore, it was necessary to develop a specific change management model for e-government projects in Indonesia. Model was develop based on methodology, that are: identify the common components; analyze the characteristics of e-government projects in Indonesia; and formulate the change management methodology. The result of the research was a specific change management model for e-government projects in Indonesia that consists of seven main components, which were set the change goal, form a change management teams, doing gap analysis, establish a desire to change, design new environments, implementing the change, and sustain the change. Regulation and leadership are the main driver of e-government project initiative in Indonesia. The components were mapped to SDLC phases and states of change